Dragonflies and damselflies of the East - Paulson, Dennis, 1937- (Princeton field guides., 2011)
This is the first fully illustrated guide to all 336 dragonfly and damselfly species of eastern North America--from the rivers of Manitoba to the Florida cypress swamps--and the companion volume to Dennis Paulson's acclaimed field guide to the dragonflies and damselflies of the West. Dragonflies and Damselflies of the East features hundreds of color photos that depict all the species found in the region, detailed line drawings to aid in-hand identification, and a color distribution map for every species--and the book's compact size and user-friendly design make it the only guide you need in th.